2018
DOI: 10.1021/acsearthspacechem.8b00098
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Reactivity of the CN Radical with Methyl Amines at Low Temperatures (23–297 K): A Combined Experimental and Theoretical Investigation

Abstract: The gas phase reactivity of the CN radical in the presence of dimethylamine (CH 3 ) 2 NH and trimethylamine (CH 3 ) 3 N has been investigated experimentally using a uniform supersonic expansion CRESU reactor coupled to the pulsed laser photolysis/laser-induced fluorescence technique. Rate constants have been obtained in the temperature range 23− 297 K and were found to be independent of temperature for both reactants. A typical rate constant of 5 × 10 −10 cm 3 molecule −1 s −1 is representative of the full set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 86 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…Anisotropic hyperfine and nuclear quadrupole tensors are traceless. subsequent work (Sleiman et al 2018a), the quantumchemical investigation was revised, thus pointing out the barrierless formation of CH 2 NH 2 + HCN. However, in (Sleiman et al 2018a), the authors did not take the attack of CN to the NH 2 side into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic hyperfine and nuclear quadrupole tensors are traceless. subsequent work (Sleiman et al 2018a), the quantumchemical investigation was revised, thus pointing out the barrierless formation of CH 2 NH 2 + HCN. However, in (Sleiman et al 2018a), the authors did not take the attack of CN to the NH 2 side into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…See, subsequent work (Sleiman et al 2018a), the quantumchemical investigation was revised, thus pointing out the barrierless formation of CH 2 NH 2 + HCN. However, in (Sleiman et al 2018a), the authors did not take the attack of CN to the NH 2 side into consideration. In the present study, we have taken a step further by investigating all possible reaction channels, thus demonstrat-ing that two other pathways are feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Ion-neutral association reactions have also been investigated in CRESU flows for C + , , N 2 + , O 2 + , CH 3 + , Ar + , NH 4 + , and H 3 O + . The ion-neutral reactions measured to date using CRESU apparatuses are listed in Table . …”
Section: Laboratory Methods For Measuring Low-temperature Reaction Ki...mentioning
confidence: 99%
“…63 Furthermore, our previous work aimed at clarifying some inconsistencies between the experiment and theory. 65,66 There, it was found that abstraction from the CH 3 group proceeds through the formation of an initial prereactive complex that evolves to yield CH 2 NH 2 and HCN as the main products, with a relative energy of −140.2 kJ mol −1 with respect to the reactant asymptote. In addition, a theoretical investigation of the rotational spectrum was carried out for the CH 2 NH 2 radical (as well as for CH 3 NH) to support its laboratory characterization.…”
Section: Chmentioning
confidence: 99%